ROUTE CONSTRUCTING FOR A MOBILE ROBOT BASED ON THE D-STAR ALGORITHM (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2024)
This paper discusses the use of the D-star algorithm to construct an optimal route for a mobile robot in a space with obstacles. We present a mathematical description of the D-star algorithm operating principle, which is based on the idea of dynamic programming and step-by-step path cost updating. Based on this description, a Python program was developed that is capable of building a route for the robot, taking into account the situation around it. To test the efficiency and accuracy of the algorithm, a number of experiments were carried out on various test maps with different obstacle configurations. The results showed that the D-star algorithm demonstrates high efficiency and reliability in constructing the optimal route for a mobile robot under various conditions.